EFEKTIVITAS MODEL PEMBELAJARAN SOLE (SELF ORGANIZED LEARNING ENVIRONMENT) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 1 BELITANG - Cindy Lestari; Agus Pahrudin,; Riyan Terna Kuswanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the effectiveness of the Self-Organized Learning Environment (SOLE) model on students’ learning outcomes in Islamic Religious Education (PAI) and Character Education at SMP Negeri 1 Belitang. The research is motivated by the low level of students’ higher-order thinking skills, limited use of interactive learning models, and low learning motivation, which result in suboptimal learning outcomes. The objective of this study is to analyze whether the SOLE model significantly improves students’ cognitive learning outcomes compared to conventional teaching methods. This research employs a quantitative approach using a quasi-experimental design, specifically the posttest-only control group design. The sample consists of two classes of eighth-grade students, where one class serves as the experimental group taught using the SOLE model, and the other as the control group taught using conventional methods. Data were collected through multiple-choice tests measuring cognitive levels (C1–C6), and analyzed using statistical tests including validity, reliability, normality, homogeneity, and independent sample t-test. The results indicate that although the SOLE model promotes active, collaborative, and independent learning, the statistical analysis shows no significant difference in learning outcomes between the experimental and control groups at the tested stage (Sig. 0.606 > 0.05). This suggests that while SOLE has potential to enhance engagement and higher-order thinking, its effectiveness in significantly improving measurable learning outcomes requires further optimization and supporting conditions such as learning facilities and implementation strategies.